Neuroart and headache: the enigmas in the Michelangelo's frescos - Valença, Marcelo Moraes (2011)
Neuroart is a discipline of Neurosciences where there is an interrelationship between art and sciences. Great names such as Leonardo da Vinci, Michelangelo, Vesalius used the art of illustration to document the human anatomy. In the present article we are commenting about hidden anatomical structures found in Michelangelo's frescos of the Sistine Chapel. We also showed the imagem of two men, expressing unilateral pain and agitation.